Propranolol Treatment of Infantile Hemangiomas: Anticipatory Guidance for Parents and Caretakers - Martin, Kari (Pediatr Dermatol, 2013)
Infantile hemangiomas (IH) are benign tumors of endothelial-like cells. Occurring in 4.5% of children, they are the most common tumor of childhood. The great majority of patients with IH will not need treatment, but 10% require systemic treatment. Many treatments have been described for the treatment of IH, but the Food and Drug Administration has not approved any. Over the last decade, numerous reports of successful treatment of IH with propranolol have been published. Despite its widespread use, little is known regarding the proper dosing, safety monitoring, and during of treatment or long-term outcomes for propranolol treatment of IH. Given its potential side effects, detailed education regarding proper administration of the medication as well as warning signs to watch for is necessary for parents and caretakers. Herein, we provide a parental handout that practitioners can individually tailor for use in their clinics when educating parents and caretakers about the use of propranolol for IH. Updates will also need to be made as more is learned regarding the optimal dosing and safety monitoring when using propranolol for this indication. FORWARD: This article is a little different from the usual Techniques for Tots which have typically focused on examination or surgical techniques. We hope the readers will find it useful as an educational tool for families whose children are receiving propranolol for infantile hemangiomas. Ilona J. Frieden M.D. Lawrence F. Eichenfield M.D. Editors, Pediatric Dermatology